2018
DOI: 10.1055/a-0659-9928
|View full text |Cite
|
Sign up to set email alerts
|

Acute Administration of Tibolone Prevents Oxidative Stress in Ovariectomized Rats Fed High-Fat-and-Fructose Diet

Abstract: In addition to oxidative stress due to the increase of free radicals, estrogen deficiency is associated with changes in enzymatic activity, glutathione redox ratio (GSH/GSSG), and the content of oxidative markers such as malondialdehyde. Tibolone, a synthetic steroid, has been used as an elective treatment for the relief of menopausal symptoms. However, the acute effects of hormonal therapy with tibolone on metabolic parameters and oxidative stress markers associated with the first stages of estrogen deficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
5
4
0
Order By: Relevance
“…Thus, our results revealed that a high fat-fructose diet increased food intake, with marked weight gain due to the caloric contribution provided by fat and carbohydrates in obese group. We also found metabolic alterations, such as increases in glucose, triglycerides, cholesterol and the HOMA-IR index, similar to other studies that have used hypercaloric diets [13,15]. Hence, our results showed that with obesity triggered dysmetabolism, hyperglycemia and hypertriglyceridemia, as well as an increase of the levels of inflammatory cytokines (TNF-α, IL-6), are present.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, our results revealed that a high fat-fructose diet increased food intake, with marked weight gain due to the caloric contribution provided by fat and carbohydrates in obese group. We also found metabolic alterations, such as increases in glucose, triglycerides, cholesterol and the HOMA-IR index, similar to other studies that have used hypercaloric diets [13,15]. Hence, our results showed that with obesity triggered dysmetabolism, hyperglycemia and hypertriglyceridemia, as well as an increase of the levels of inflammatory cytokines (TNF-α, IL-6), are present.…”
Section: Discussionsupporting
confidence: 91%
“…One of the main organs affected by obesity is the liver, where long-term increases in lipogenesis and decreases in mitochondrial β-oxidation of nonesterified fatty acids, as well as hepatic triglyceride secretion, can contribute to fat accumulation in the liver, leading to the appearance of liver steatosis. Additionally, in a prospective longitudinal study, 86% of patients with NAFLD and progressive fibrosis were obese [14,15,21]. At the renal level, changes such as pelvic dilation were found in 50% of the obese group rats.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results revealed that a high fat-fructose diet increased food intake, with marked weight gain due to the caloric contribution provided by fat and carbohydrates in obese group. We also found metabolic alterations, such as increases in glucose, triglycerides, cholesterol and the HOMA-IR index, similar to other studies that have used hypercaloric diets [14,15]. Hence, our results showed that with obesity triggered dysmetabolism, hyperglycemia and hypertriglyceridemia, as well as an increase of the levels of in ammatory cytokines (TNF-a, IL-6), are present.…”
Section: Discussionsupporting
confidence: 91%
“…One of the main organs affected by obesity is the liver, where long-term increases in lipogenesis and decreases in mitochondrial β-oxidation of nonesteri ed fatty acids, as well as hepatic triglyceride secretion, can contribute to fat accumulation in the liver, leading to the appearance of liver steatosis. Additionally, in a prospective longitudinal study, 86% of patients with NAFLD and progressive brosis were obese [13,15,21].…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, the results of this experimental model of obesity revealed alterations in metabolic parameters, such as lipids and HOMA-IR index, as mentioned by other studies where the use of hypercaloric diets similar to that used in this study, is associated with the early onset of lipidlike metabolic alterations [13], besides the endothelial damage that is had with the intake of hypercaloric diets, showing increase in TNF-α and adhesion molecules (ICAM-1 y VCAM-1). Together, with the ultrasound evaluation, the alterations of joint cysts and liver damage are highlighted.…”
Section: Discussionsupporting
confidence: 84%